Answer:
B) x = -6 and x = 2
Explanation:
![(3x+9)/(x^(2)+4x-12)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/i7rhzon1u87fn55546anen8ve3om2hofyj.png)
can be rewritten as
![(3x+9)/((x+6)(x-2))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/px0qhdcjhzyboad3vwbrznniix7ss1lt1z.png)
because
-2 · 6 = -12
-2 + 6 = -4
so thats why the denominator is (x+6)(x-2)
A vertical asymptote is where the denominator equals 0, so,
-6 + 6 = 0
2 + -2 = 0
So the Answer is:
B) x = -6 and x = 2